Comparative Study of Rectifier Topologies for Quasi-Z-Source Derived Push-Pull Converter - Chub, A.; Husev, O.; Vinnikov, D. (Elektronika ir Elektrotechnika, 2014)
Quasi-Z-source derived push-pull converter is a new topology intended for energy harvesting from renewable energy sources. Use of the topology shows that currents in the input and output parts strongly depend on the implementation of the output rectifier. This paper presents a comparative study and an experimental evaluation of the four output rectification stages. Analytical expressions for the voltage and current stress of rectifier components are presented. Experimental verification with the 400 W prototype was performed in the input voltage range of 40 V to 400 V at 400 V output voltage. Efficiency and duty cycle of active state, i.e. the DC gain characteristic, were measured in that range. Experimental waveforms for each topology are presented. Waveforms were measured at the input voltage 80 V, i.e. at the DC gain factor equal to 5. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7264